Index of Orthodontic Treatment Need of Patients undergoing Orthodontic Treatment at BPKIHS, Dharan - Gyawali, Rajesh; Pokharel, Prabhat Ranjan; Giri, Jamal; Shrestha, Gunjan Kumar; Bhattarai, Bhushan (Orthodontic Journal of Nepal, 2016)
Introduction: Measurement of the severity of malocclusion is assessed with various indices among which Index of Orthodontic Treatment Need (IOTN) is widely used for clinical and epidemiological purpose. Objective: To find out the treatment need of patients who are undergoing orthodontic treatment. Materials & Method: 207 patients (71 male, 136 female) fulfilling the inclusion criteria were assessed for the dental health component (DHC) and aesthetic component (AC) of the Index of Orthodontic Treatment Need (IOTN) by a single investigator. DHC was assessed with study models, whereas AC with intraoral frontal photograph. Result: Examination of DHC showed that 1 patient (0.5%) had no need; 20 patients (9.7%) had mild/little need; 50 patients (24.2%) had moderate/borderline need; 97 (46.9%) had severe need; 39 patients (18.8%) had extreme treatment need. Similarly, 7 patients (3.4%) had AC 1; 18 patients (8.7%) had AC 2; 13 patients (6.3%) had AC 3; 32 patients (15.5%) had AC 4; 34 patients (16.4%) had AC 5; 25 patients (12.1%) had AC 6; 18 patients (8.7%) had AC 7; 35 patients (16.9%) had AC 8; 15 patients (7.2%) had AC 9; 10 patients (4.8%) had AC 10. Conclusion: Among the patients who were undergoing orthodontic treatment, majority were in severe/extreme treatment need, however few with no treatment need were also found. Orthodontic Journal of Nepal, Vol. 6 No. 1, June 2016, pp.23-26